Avaliação do conhecimento tradicional da indicação geográfica denominação de origem terra indígena Andirá-marau - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The work discusses aspects inherent to the evaluating of the Geographical Indication species Denomination of Origin Terra Indígena Andirá-Marau, seeking to understand how much traditional knowledge added to this intellectual property asset benefits native peoples after their recognition. Its general objective is to examine the contribution of traditional knowledge in the Geographical Indication Terra Indígena Andirá-Marau through an evaluation after recognition of the Geographical Indication (Post-GI). It adopts qualitative research of applied nature as a methodological perspective, employing bibliographic and documentary techniques. It points out that methodologies focused on post-GI evaluations are incipient, especially regarding the associated traditional knowledge. It argues that traditional indigenous knowledge is preserved when linked to intellectual property, which can assure the originating communities of the benefits of managing these resources that can be developed. In this sense, Geographical Indication is one of the ways to do it. Thus, it presents, as a result, a proposal for evaluation of the Denomination of Origin Terra Indígena Andirá Marau of the Sateré-Mawé peoples for the native guarana (waraná). It should be noted that the experts validated the proposed instrument consulted. Among the consultation results, it was identified that there is not a single type of evaluation of Geographical Indication but a combination of typologies appropriate to each reality. The instrument proposed and validated allowed us to scale the traditional knowledge of this GI and made it possible to understand that traditional knowledge cannot be measured concretely.
Keywords: Nativos - Amazônia; Mawé (Povo indígena); CIENCIAS HUMANAS; Propriedade Intelectual; Sateré-Mawé; Waraná; Instrumento de avaliação